Isoliquiritigenin Inhibits Metastatic Breast Cancer Cell-induced Receptor Activator of Nuclear Factor Kappa-B Ligand/Osteoprotegerin Ratio in Human Osteoblastic Cells - Lee, Sun Kyoung (Korean Society of Cancer Prevention, 2015)
Bone destruction induced by the metastasis of breast cancer cells is a frequent complication that is caused by the interaction between cancer cells and bone cells. Receptor activator of nuclear factor kappa-B ligand (RANKL) and the endogenous soluble RANKL inhibitor, osteoprotegerin (OPG), directly play critical roles in the differentiation, activity, and survival of osteoclasts. In patients with bone metastases, osteoclastic bone resorption promotes the majority of skeletal-related events and propagates bone metastases. Therefore, blocking osteoclast activity and differentiation via RANKL inhibition can be a promising therapeutic approach for cancer-associated bone diseases. We investigated the potential of isoliquiritigenin (ISL), which has anti-proliferative, anti-angiogenic, and anti-invasive effects, as a preventive and therapeutic agent for breast cancer cell-induced bone destruction. ISL at non-toxicity concentrations significantly inhibited the RANKL/OPG ratio by reducing the production of RANKL and restoring OPG production to control levels in hFOB1.19 cells stimulated with conditioned medium (CM) of MDA-MB-231 cells. In addition, ISL reduced the expression of cyclooxygenase-2 in hFOB1.19 cells stimulated by CM of MDA-MB-231 cells. Therefore, ISL may have inhibitory potential on breast cancer-induced bone destruction.